Bunching on the Autobahn? Speeding Responses to a 'Notched' Penalty Scheme - Christian Traxler; Franz Westermaier; Ansgar Wohlschlegel (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper studies drivers' responses to a `notched' penalty scheme in which speeding penalties are stepwise and discontinuously increasing in speed. We present survey evidence suggesting that drivers in Germany are well aware of the notched penalty structure. Based on a simple analytical framework we analyze the impact of the notches on drivers' optimal speed choices. The model's predictions are confronted with data on more than 150,000 speeding tickets from the Autobahn and 290,000 speed measures from a traffic monitoring system. The data provide evidence on modest levels of bunching, despite several frictions working against it. We analyze the normative implications and assess the scope for welfare gains from moving from a simple, notched penalty scheme to a more complex but less salient Pigouvian scheme.
Keywords: K40; D04; 330; notches; speeding tickets; stepwise penalty function; salience